Older postmenopausal women with lower lean mass have hypermethylated sites in the PI3K-Akt pathway - Correia, Igor Massari; da Silva Rodrigues, Guilherme; Noronha, Natália Yumi; Watanabe, Lígia Moriguchi; Luciano de Almeida, Mariana; Sobrinho, Andressa Crystine da Silva; Nonino, Carla Barbosa; Bueno Júnior, Carlos Roberto (Frontiers in Physiology, 2023)
Introduction: The decrease in lean mass is directly related to the loss of independence, muscle strength, and worse quality of life over the years. Although the genetic determinants of muscle mass were well recognized, recent literature has been uncovering new epigenetic factors affecting the state of muscular tissue. This study aimed to verify differences in the DNA methylation profile among Brazilian postmenopausal women aged 50–70 years according to the lean mass evaluation. Methods: A cross-sectional study comprised 40 women aged 50–70 years. After K-means cluster analysis the 40 participants were divided into two groups, the Lower Lean Mass group with 20 participants (61.1 ± 4.6 years) and the Higher Lean Mass group with 20 participants (60.7 ± 3.2 years). Lean mass was measured by dual-energy X-ray emission densitometry (DEXA). The participants' DNA was extracted using the Salting Out technique and subsequently, the Illumina 850k EPIC Infinium Methylation BeadChip was performed to obtain methylation data. Results: We obtained 1,913 differentially methylated sites (p ≤ 0.005 of β > 5% and β < −5%) in a total of 979 genes between groups (p ≤ 0.005; −5% > β > 5%). In addition, the PI3K-Akt pathway had the greatest power of significance with an FDR of 4.6 × 10–3. Conclusion: Our results demonstrate a differentiation between specific sites of different genes, which have essential functions in body composition and energy metabolism, supporting future studies that aim to relate lean mass with epigenetics.